Primary Outcomes in Two Randomized Controlled Trials of Treatments for Cannabis Use Disorders - Peters, Erica N. (2011)
BACKGROUND: While several randomized controlled trials evaluating a range of treatments for cannabis use disorders have appeared in recent years, these have been marked by inconsistency in selection of primary outcomes, making it difficult to compare outcomes across studies. METHOD: With the aim of identifying meaningful and reliable outcome domains in treatment studies of cannabis use disorders, we evaluated multiple indicators of marijuana use, marijuana problems, and psychosocial functioning from two independent randomized controlled trials of behavioral treatments for cannabis use disorders (Ns = 450 and 136). RESULTS: Confirmatory factor analysis indicated that the best-fitting model of outcomes in both trials encompassed three distinct factors: frequency of marijuana use, severity of marijuana use, and psychosocial functioning. In both trials, frequency of marijuana use and longest period of abstinence during treatment were most strongly associated with outcome during follow-up. Using two categorical definitions of “clinically-significant improvement,” individuals who demonstrated improvement differed on most end-of-treatment and long-term outcomes from those who did not improve. CONCLUSIONS: Results may guide future randomized controlled trials of treatments for cannabis use disorders in the collection of relevant end-of-treatment outcomes and encourage consistency in the reporting of outcomes across trials.